Early Detection of Non-Communicable Diseases Through Free Health Check-Ups in Kolam Village, Percut Sei Tuan District Percut Sei Tuan - Zulfahri Lubis; Kristina; Kamaliah Ainun; Syamsul Idris; Yusridawati (PT Bukuloka Literasi Bangsa, 2025)
Non-communicable diseases (NCDs) are diseases that cannot be transmitted from one person to another and usually develop over a long period of time. One of the factors causing the development of non-communicable diseases is a lack of knowledge and awareness of the dangers of NCDs, which leads to people not undergoing health checks. This is also caused by people's reluctance to get checked until they feel sick. One way to prevent non-communicable diseases is to undergo regular health checks. Therefore, it is necessary to prevent NCD risk factors through health checks and health education. This activity was then carried out using three methods, namely direct practice to check the health of participants, providing health education, and finally administering herbal medicine. Overall, the results of the health examinations varied from normal, mild, moderate, to severe. It is hoped that with activities such as this, the community will become more aware of the importance of regular health tests for early detection of NCDs. Keywords: Health Check-up, Non-Communicable Diseases